Influence Price Discounts to Impulse Buying on Consumers Indomaret Village Tonronge Subdistrict Baranti Regency Sidenreng Rappang - Putri Nur Sabrina Natasya; Aris Baharuddin; Bakhtiar; Fitriana (Fakultas Ilmu Sosial dan Hukum, 2025)
This study aims to determine how price discounts affect impulse buying among consumers at Indomaret in Tonronge Village. This research uses quantitative research methods to measure the influence of one variable on another statistically and objectively. Data collection techniques were carried out through observation and questionnaires distributed directly to consumers who shop at the location. The sample used in this study was determined using the Slovin formula, resulting in a total of 100 respondents who were considered representative of the consumer population. The data obtained from the field were processed using SPSS 26, which included several analytical procedures such as validity tests, reliability tests, descriptive statistical analysis, and inferential statistical analysis. These analyses were conducted to ensure that the research instruments were accurate and that the relationship between variables could be tested properly. The research results show that the price discount variable has a positive and significant effect on the impulse buying variable among Indomaret consumers in Tonronge Village, Baranti Subdistrict, Sidenreng Rappang Regency. This finding is supported by simple linear regression analysis, which confirms the strength of the relationship between the two variables. Furthermore, the coefficient of determination indicates that price discounts influence impulse buying behavior by 84.1%, demonstrating a very strong contribution of price discounts to unplanned purchasing decisions among consumers in the research area.